A case study of ergonomics encompassing white-collar workers: anthropometry, furniture dimensions, working posture and musculoskeletal disorders - Ângela C. Macedo, Cátia F. Azenha, Ana P. Brito (2014)
office workers, occupational health, ergonomics, RULA, pain